PENGENDALIAN DISTRIBUSI GAS BERSUBSIDI DI KOTA PEKANBARU - Fadilah Mukmin; Zulkarnani " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
LPG (Liquefied Petroleum Gas) three kilogram tube is a subsidized gas intended for lower class households and micro enterprises. Distribution is done by Pertamina, then distributed to the agency, and the last channeled to the base. The base party may only sell to lower-class and micro-businesses only with the selling price as regulated by the Pekanbaru City Government, and furthermore, the base is prohibited from selling to retailers. This study aims to determine how the control of the distribution of subsidized gas in Pekanbaru City and the factors that influence the control of the distribution of subsidized gas. The theory used in this research is about the control by Stoner and Wankel in Siswanto. The indicators are to define the desired results, define the results predictors, define standards for predictors and outcomes, define information and feedback networks, and assess information and take remedial action. And to know the factors that affect the control of the distribution of subsidized gas is based on field research. The method used in this research is descriptive qualitative with purposive sampling technique. Informants in this research are Head of Trade and Head of Information and Legal Section of Trade Office and Industry of Pekanbaru City, Subsidized Gas Agency, Subsidized Gas Base, and Community as consumer of subsidized gas with accidental sampling. And data analysis used is descriptive qualitative. The results showed that the control of the distribution of subsidized gas conducted by the Department of Trade and Industry Pekanbaru City has not been maximized. This can be seen from the existence of bases that sell subsidized gas is not on target. The base sells subsidized gas to the retailers and sells it above the set price. And it is evident from the public as consumers of subsidized gas still buy the subsidized gas at retailers. Factors affecting the control of the distribution of subsidized gas are limited human resources, lack of coordination, lack of advice and infrastructure, and the assumption that the base is aware of and obeys the rules.Keywords: Control, Distribution, Subsidized Gas